Improvements and Future Challenges in the Field of Genetically Sensitive Sample Designs - Frank M. Spinath (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Understanding the sources of individual differences beyond social and economic effects has become a research area of growing interest in psychology, sociology, and economics. A quantitative genetic research design provides the necessary tools for this type of analysis. For a state-of-the-art approach, multigroup data is required. Household panel studies, such as BHPS (Understanding Society) in the UK or the SOEP in Germany, combined with an oversampling of twins, provide a powerful starting point since data from a reasonably large number of non-twin relatives is readily available. In addition to advances in our understanding of genetic and environmental influences on key variables in the social sciences, quantitative genetic analyses of target variables can guide molecular genetic research in the field of employment, earnings, health and satisfaction, as combined twin and sibling or parent data can help overcome serious caveats in molecular genetic research.
Keywords: B40; B49; C51; C83; 330; Genetics; twins; psychology; sociology; economics; heritability; environment; multigroup design; BHPS; SOEP